Enhancement of Cortical Network Activity in vitro and Promotion of GABAergic Neurogenesis by Stimulation with an Electromagnetic Field with a 150 MHz Carrier Wave Pulsed with an Alternating 10 and 16 Hz Modulation - Gramowski-Voß, Alexandra; Schwertle, Hans-Joachim; Pielka, Anna-Maria; Schultz, Luise; Steder, Anne; Jügelt, Konstantin; Axmann, Jürgen; Pries, Wolfgang (Frontiers in Neurology, 2015)
In recent years, various stimuli were identified capable of enhancing neurogenesis, a process which is dysfunctional in the senescent brain and in neurodegenerative and certain neuropsychiatric diseases. Applications of electromagnetic fields to brain tissue have been shown to affect cellular properties and their importance for therapies in medicine is recognized. In this study, differentiating murine cortical networks on multiwell microelectrode arrays were repeatedly exposed to an extremely low electromagnetic field (ELEMF) with alternating 10 and 16 Hz frequencies piggy-backed onto a 150 MHz carrier frequency. The ELEMF exposure stimulated the electrical network activity and intensified the structure of bursts. Further, the exposure with an electromagnetic field within the first 28 days of the differentiation the network activity induced also reorganization within the burst structure. This effect was already most pronounced at 14 days in vitro after 10 days of exposure. Overall, the development of cortical activity under these conditions was accelerated. These functional electrophysiological changes were accompanied by morphological ones. The percentage of neurons in the neuron glia co-culture was increased without affecting the total number of cells, indicating an enhancement of neurogenesis. The ELEMF exposure selectively promoted the proliferation of a particular population of neurons, evidenced by the increased proportion of GABAergic neurons. The results support the initial hypothesis that this kind of ELEMF stimulation is a treatment option for specific indications with promising potential for CNS applications, especially for degenerative diseases such as Alzheimer’s disease and other dementias.